Overview on recent photovoltaic module cooling methods: advances PVT systems - Nurul Shahirah Binti Rukman; Ahmad Fudholi; Ivan Taslim; Merita Ayu Indrianti; Intan Noviantari Manyoe (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Renewable energy had been monopolized the research area in these past decade up till nowadays, due to its reliability and future in global production of electrical and thermal energy. Narrowing down the scope to the photovoltaic thermal (PVT) system, lots of improvements had been implied both theoretically and experimentally. One of the most attractive applications of PVT water or air-based collectors is building integrated photovoltaic thermal (BIPVT) system, which has undergone rapid developments in recent years. This review paper comprises the research findings on the improvements that had been integrated by PVT systems as well as well as personal and cited remarks on advancements on cooling techniques on PVT system.